Prediction value of pulmonary hypertension in newly identified left ventricular dysfunction among adult patients after patent ductus arteriosus closure. (November 2019) - Chen, Peng-yuan; Luo, Dong-ling; Li, He-zhi; Fei, Hong-wen; Huang, Tao; Huang, Yi-gao; Chen, Ji-mei; Zhuang, Jian; He, Peng-cheng; Zhang, Cao-jin
The present study aimed to propose the pulmonary hypertension for predicting left ventricular dysfunction in adults after patent ductus arteriosus closure. A total of 183 patients (age ≥18 years) after patent ductus arteriosus occlusion were retrospectively collected in this study. In brief, pre-, post-procedure and short-term follow-up transthoracic echocardiography were performed. Simpson's method was used to measure the left ventricular ejection fraction (LVEF), and LVEF less than 50% after procedure was utilized as a criterion to identify left ventricular dysfunction. As a result, 36 (19.67%) patients developed newly identified left ventricular dysfunction. The rate of newly identified left ventricular dysfunction was significantly higher in moderate or severe pulmonary hypertension groups compared to the groups of mean pulmonary artery pressure (mPAP) <25 mmHg (P < .001). Logistic regression analysis showed that elevated mPAP ( ≥25 mmHg) was an independent predictive value for newly identified left ventricular dysfunction (OR = 3.584, 95%CI: 1.186–10.832, P = .024) after adjusting confounders. The ROC curve revealed a good discrimination power for predicting newly identified left ventricular dysfunction (AUC = 0.924, 95%CI: 0.885–0.963, P < .001). Taken together, newly identified left ventricular dysfunction after patent ductus arteriosus closure was prevalent in patients with elevated mPAP. The pre-procedure elevated mPAP is an independent risk factor for the prediction of the newly identified left ventricular dysfunction in adult patients undergoing percutaneous patent ductus arteriosus closure. It is feasible to propose a risk model for predicting post-procedure left ventricular dysfunction and a heart function monitoring in pulmonary hypertension patients.